Unbundling water and land rights in Kilifi County, Kenya: a gender perspective - Hillesland, Marya; Doss, Cheryl R.; Mutua, Mercy; Guettou Djurfeldt, Nadia; Nchanji, Eileen; Twyman, Jennifer; Korzenevica, Marina (Frontiers in Human Dynamics, 2023)
Feminist scholars and activists have drawn attention to the importance of women's land rights, and studies focused on irrigation have explored the gendered relationships between land and water rights. Yet little of this work has focused on the relationship between land and water rights for domestic and productive purposes more broadly. Within rural communities, women and men have different rights to both land and water. We explore these interconnected relationships using community profiles, focus group discussions, and in-depth interviews from two communities as well as survey data collected from multiple adult members of rural households in Kilifi County, Kenya. Using a bundle of rights framework, we find that few individuals hold the complete bundle of rights over water, and the extent to which the rights are acknowledged by others and enforceable varies by the land-water tenure system. The full bundle of rights to water is most likely to be complete and most robust for men who have private water points on household land they hold. Even then, other people may assert claims to the water on the water point, although these claims may involve negotiation or payment. Many of the rights to water points across the land-tenure systems are shared with others rather than being held by one individual. As such, the ability to negotiate water access is particularly important. The duration of the rights, or the length of time for which the rights are held, is embedded in social relations and exchange, particularly on others' household land. Women more than men seem to maintain a complicated set of social networks that allow them to negotiate for water from other women who manage the water transactions. The process of negotiation needs to be re-articulated each time. Thus, the duration of these rights on these water points depends on the ongoing relationships.